The E-MOTIVE Trial – game changer for PostPartum Haemorrhage (PPH) management focusing on early detection and timely interventions (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Abstracts not available Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 61-64